Effectiveness of Educational Videos on Reducing Anxiety in Pre-Anesthesian Patients - Sari, Ni Kadek Nirmala; Maharyawan, I Wayan Agus; Lewar, Emanuel Ileatan; Devi, Ni Luh Putu Lusiana (Journal of Language and Health, 2024)
Surgery and anesthesia are actions that can cause problems for someone who will undergo them, one of the problems that is often found is anxiety. Several research results report that anxiety can affect 60-80% of patients undergoing surgery. Objective: To determine the effectiveness of health education using video media in reducing preoperative patient anxiety. Method:This research uses a pre-experimental method with one group pretest and posttest design. This research was conducted in March-April 2023 at Buleleng Regional Hospital. The sample in this study involved 42 patients undergoing elective surgery. The research instrument was a questionnaire sheet which was then analyzed using the Kolmogorov – Smirnov statistical test. Results:Providing complete anesthesia education was 42 (100.0%) respondentsn. The results of the pre-education research on gold were 23 (54.8%) respondents who were seriously anxious, 16 (38.1%) respondents were moderately anxious, 2 (4.8%) respondents were very anxious, 1 (2.4%) respondent was mildly anxious. The results of the post-education research were 25 (59.5%) respondents who were seriously anxious, 14 (33.3%) respondents were moderately anxious, 2 (4.8%) respondents were very anxious, and 1 (2.4%) respondent was mildly anxious. Conclusion:Effectiveness of educational videosanesthesia is able to increase patient understanding and knowledge so that it can reduce the anxiety level of pre-anesthesia patients at Buleleng Regional Hospital.